New flooded rice cultivars for the state of Rio de Janeiro, Brazil - Amorim Neto, Silvino; Eustáquio de Bastos Andrade, Wander; Marta Bellon Fernandes, Glória; Alves da Costa, Renato (Pesquisa Agropecuaria Brasileira, 1998)
In the recent years, a significant reduction in the cultivated rice area in the State of Rio de Janeiro, Brazil, was reported. However, with the use of cultivars indicated by research, as well as many other technologies to achieve high grain yield, the average rice grain yield increased from 1,800 kg/ha to 3,474 kg/ha, while production has been maintained around 100,000 ton. With the objetive of evaluating new rice genotypes, 23 field experiments were carried out from 1985 to 1993, in the North, Northwest and low coast land region, using either direct sowing or seedling transplant. On the whole, the average grain yield obtained with the P 1377-1-15M-32-2-1 and CNA 5551 genotypes was similar to the local cultivar, INCA 4440. They also showed the same plant height, earlier crop growth and best grain quality. In the low coast land region, these genotypes were resistant to rice blast (Pyricularia grisea Cav.), a disease that occurs frequently in that region. Based on these results, the P 1377-1-15M-32-2-1 and CNA 5551 genotypes are recommend for extensive use in the State of Rio de Janeiro, as PESAGRO 106 and PESAGRO 107 cultivars, respectively.